Trust aware nature inspired optimised routing in clustered wireless sensor networks. (14th August 2019) - Gilbert, Edwin Prem Kumar; Baskaran, K.; Rajsingh, Elijah Blessing; Lydia, M.; Selvakumar, A. Immanuel
Wireless sensor networks (WSN) consist of sensor nodes which have capabilities of sensing, computation and communication. Routing algorithms are required in a WSN when a node is unable to send a data to the base station directly. In this paper, a trust aware optimised compressed sensing-based data aggregation and routing algorithm has been proposed for clustered WSN. Compressed sensing is used for data aggregation from sensor nodes with reduced overhead. Nature inspired optimisation has been implemented to obtain trade-off between transmission distance, hop-count, number of transmitted message and most trusted path using artificial bee colony algorithm, ant colony optimisation, differential evolution, firefly algorithm and particle swarm optimisation. Trust-based reconstruction of the compressed data is done at the base station in the presence of malicious nodes.